3-methylcrotonyl-CoA carboxylase deficiency: clinical, biochemical, enzymatic and molecular studies in 88 individuals - Grünert, Sarah; Kölker, Stefan (Orphanet journal of rare diseases, 2012)
Isolated 3-methylcrotonyl-CoA carboxylase (MCC) deficiency is an autosomal recessive disorder of leucine metabolism caused by mutations in MCCC1 or MCCC2 encoding the α and β subunit of MCC, respectively. The phenotype is highly variable ranging from acute neonatal onset with fatal outcome to asymptomatic adults.